Lungfibros hos hund : fallbeskrivningar, histopatologi samt analys av surfaktantproteiner - Eriksson, Maria (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2008)
Idiopathic pulmonary fibrosis (IPF) is a chronic respiratory disease with an estimated incidence of 3-6 cases per 100 000 inhabitants in Sweden. There is no cure for the disease, which inevitably leads to death. A similar disease has been found among terrier dogs, with an especially high prevalence in the West Highland White Terrier (WHWT). Dogs with pulmonary fibrosis become lethargic with exercise intolerance, and in some cases they develop cough and respiratory distress. This thesis gives a brief review of the field of pulmonary fibrosis and presents a method for analyzing surfactant proteins in bronchoalveolar lavage (BAL) in the dog. Five cases of canine pulmonary fibrosis are presented with clinical data, histopathology and surfactant analysis. The results show that one of the dogs with pulmonary fibrosis lacks detectable surfactant protein C (SP-C) levels in BAL, which also has been shown in humans diagnosed with a familiar form of IPF.